Skills and the Diffusion of Innovations from Britain in the Eighteenth Century. (December 1975) - Mathias, Peter
Abstract : This paper stems from an initial interest in the relationships between science and technology in the eighteenth century. Hence its concern lies principally with the nature of technical innovation and the sources of technical change during the Industrial Revolution. Exploring the ways in which new technology is diffused can shed light on the nature of technical change itself, which is a complex amalgam of influences governing invention, innovation (the bringing of inventions into productive use) and the diffusion of new techniques. Taking as a topic the diffusion of technology, particularly in machine-making and engineering, between Britain and Europe in the late eighteenth century is thus not meant to be a peg on which to hang wide-ranging animadversions on the differing economic fortunes and pace of advance of Britain and Europe, or a discussion of why industrialization came first and fastest to Britain and lagged elsewhere: it is a much narrower enquiry into seeing what light the processes and difficulties of diffusing new technology cast upon technical change itself at this time.